Authentication Techniques in 5G Network Slicing Security: A Survey - Essam A. Abduh; Belal A. Al-Fuhaidi; Fahd A. Alqasemi (University of Science and Technology, Sana'a, Yemen, 2024)
Emerging network slicing technology is a key feature of 5G cellular networks. Network slice and cloud computing provide promising solutions in 5G architecture. Network Slicing Security (NSS) is also important in 5G research. The emerging environment is a fertile breeding ground for the attacker. This study discusses authentication techniques in fifth-generation networks, as the authentication process is the first wall of defense against various network attacks. Meanwhile, techniques and algorithms are important in achieving confidentiality, integrity, and availability while maintaining speed and accuracy. The diversity and multiplicity of devices, in addition to the movement between slices and operators, make the authentication process extremely important. This article presents and explains the main issues related to network segment threats and attacks, highlighting the authentication techniques used in NS. The authentication process mainly focuses on the use of encryption and digital signature technology, either implicitly within the devices or directly when connecting to the network.